The expiration of a tax decision which became irrelevant - Olesińska, Agnieszka (Studia Iuridica Toruniensia, 2021)
According to Article 258 § 1 item 1 of Polish Tax Ordinance Act of 29 August 1997, a tax authority that has issued a decision confirms its expiry if it has become irrelevant (groundless). The main question is, if a decision expires after the lapse of the limitation period of a tax liability. The Author discusses the scope of a term ‘irrelevant’ (groundless) used in Article 258 in comparison with Article 208 § 1 which states, that if proceedings become groundless for whatever reason, in particular after the lapse of the limitation period of a tax liability, a tax authority issues a decision to terminate the proceedings.